2013
DOI: 10.1038/labinvest.2013.61
|View full text |Cite
|
Sign up to set email alerts
|

Immune complexes activate human endothelium involving the cell-signaling HMGB1-RAGE axis in the pathogenesis of lupus vasculitis

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the formation of immune complexes (ICs), which contain a complex mixture of autoantigens nucleic acids, nucleic acids-associated proteins and corresponding autoantibodies. In SLE, ICs are deposited in multiple organs. Vasculopathy and vasculitis in SLE are typical complications and are associated with deposition of ICs on endothelium, endothelial activation and inflammatory cell infiltration. However, the effects of ICs on endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Interestingly, in this model, autoantibody production involves TLR2, one of the receptors for HMGB1. In addition to these activities, complexes can also interact with RAGE on endothelium to create the vasculopathy that marks the course of SLE (63).…”
Section: Extracellular Environment During Cell Deathmentioning
confidence: 99%
“…Interestingly, in this model, autoantibody production involves TLR2, one of the receptors for HMGB1. In addition to these activities, complexes can also interact with RAGE on endothelium to create the vasculopathy that marks the course of SLE (63).…”
Section: Extracellular Environment During Cell Deathmentioning
confidence: 99%
“…However, low molecular weight immune complexes (referred to below as small immune complexes, SIC) are believed to be less efficiently cleared by liver and spleen macrophages, which can result in the activation of neutrophils and monocytes (Jancar and Crespo; Jönsson et al, 2013; Mayadas et al, 2009), complement (Merle et al, 2015), endothelial cells (Sun et al, 2013) and mast cells (Daha et al, 1988). Immune complexes also deposit in tissues, either as a result of increased vascular permeability or tissue damage (Binstadt et al, 2006; Stokol et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, incubating human monocyte-derived macrophages with HMGB1-nucleosome complexes induced cytokine production, which could be blocked by adding box A. Whereas these studies focused on effects of HMGB1 on lymphocytes, Sun et al (33) investigated the effect of HMGB1-containing immune complexes on human endothelial cells. They showed that stimulating endothelial cells with immune complexes from SLE patients increased proinflammatory cytokines such as IL-6 and IL-8.…”
Section: Complexed Forms Of Hmgb1mentioning
confidence: 99%